Changes in the Biochar Chemical Structure during the Low-Temperature Gasification of Mallee Biochar in Air as Revealed with Fourier Transform Infrared/Raman and X-ray Photoelectron Spectroscopies - Wang, Shuai; Wu, L.; Hu, X.; Zhang, Lei; Li, T.; Jiang, S.; O'Donnell, Kane; Buckley, Craig; Li, Chun-Zhu (American Chemical Society, 2018)
Structural changes in partially gasified char during low-temperature gasification in air were investigated using Fourier transform infrared/Raman and X-ray photoelectron spectroscopies. Two kinds of chars prepared from the gasification of mallee wood in 15% H2O-Ar at 600 and 900 °C were gasified in air at 375 °C in a thermogravimetric analyzer, separately. The breakage of large aromatic ring systems, the consumption of cross-linking structures, and the formation of dangling structures indicated the destruction of the aromatic ring systems of char with the progress of gasification in air. In addition, the oxidation of char was very significant at the initial stage (char conversion of <10%) of gasification in air, which was mainly due to the newly formed aromatic C-O structures. The newly formed aromatic C-O structure was also mainly responsible for the continuously increased total oxygen content, the total Raman intensity, and the total infrared (IR) intensity of char with the progress of gasification in air. Moreover, because of the different structural stabilities between the char prepared at 600 and 900°C, two kinds of aromatic C-O structures were formed during gasification in air. Some could greatly enhance the Raman scattering ability, while some could promote the IR absorption of the char.